Gender dan Kerentanan Pekerja Anak di Kota Makassar - Abd Naris Agam; Sartika Dwi Hardiyanti (MAN 4 Kota Pekanbaru, 2026)
This article examines gendered vulnerability to child labour in Makassar City using empirical secondary data from official statistics and local social-sector records. The study applies a descriptive quantitative approach supported by document analysis of Sakernas 2024, BPS Makassar publications, BPS national child-labour tables, and Satu Data Makassar social data. It also uses an indicative estimation approach by applying the provincial child-labour prevalence to the estimated population aged 10-17 in Makassar; therefore, the estimate is interpreted as a vulnerability signal rather than an official city-level count. The findings show that Makassar has a large adolescent population, while South Sulawesi recorded a relatively high child-labour prevalence of 5.28 percent in 2024. Gendered labour-market patterns are evident: women’s labour-force participation is far below men’s, and women are highly concentrated in unpaid household responsibilities. Local records also show child street, neglected-child, and violence cases that require integrated social welfare responses. The article argues that child-labour prevention in Makassar should combine household economic protection, gender-sensitive case management, school retention, and community-based outreach.